Bloody Sunday - Coes, Ben (New York : St. Martin's Press, 2018)
"North Korea, increasingly isolated from most of the rest of the world, is led by an absolute dictator and a madman with a major goal-- he's determined to launch a nuclear attack on the United States ... Their missiles are improving, reaching a point where the U.S. absolutely must respond. What the U.S. doesn't know is that North Korea has made a deal with Iran. In exchange for effective missiles from Iran, they will trade nuclear triggers and fissionable material--an exchange, if it goes through, that will create two new nuclear powers, both with dangerous plans"--
Keywords: Andreas, Dewey -- Fiction; Intelligence officers -- Fiction -- United States; Nuclear weapons -- Fiction -- Iran; Nuclear weapons -- Fiction -- Korea (North); Thrillers (Fiction); Spy fiction